2018
DOI: 10.1111/ane.12893
|View full text |Cite
|
Sign up to set email alerts
|

Motor subtypes and other risk factors associated with drooling in Parkinson's disease patients

Abstract: Drooling is common, even in mild-to-moderate PD patients. PD patients with non-TD subtype are at a higher risk of drooling. Male sex, motor severity, excessive daytime sleepiness, poor nighttime sleep, and constipation are also associated with drooling in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…They found disease-associated increase in numerous immune and angiogenesis mediators, but only in the stool of female PD patients while the stool of male patients did not differ significantly from controls [23]. Female PD patients have also shown higher predisposition to develop critical dysphagia [24], whereas male patients are more prone to severe drooling [25].…”
Section: Non-motor Symptomsmentioning
confidence: 98%
“…They found disease-associated increase in numerous immune and angiogenesis mediators, but only in the stool of female PD patients while the stool of male patients did not differ significantly from controls [23]. Female PD patients have also shown higher predisposition to develop critical dysphagia [24], whereas male patients are more prone to severe drooling [25].…”
Section: Non-motor Symptomsmentioning
confidence: 98%
“…5 In an early PD population [disease duration 3.5 years in patients with drooling ( n = 320)], male sex, motor severity, excess daytime sleepiness, impaired sleep quality, constipation, and nontremor-dominant subtype were among the clinical factors associated with worsened drooling. 25 With advanced PD [disease duration 5 years in patients with drooling ( n = 273)], drooling was associated with higher frequencies of speech disturbances and dysphagia, and increased severity of motor and nonmotor symptoms, depression and anxiety. 26 The mechanism of drooling in PD is multifactorial and includes reduced salivary swallowing and facial hypomimia, that, when severe, can lead to dribbling of accumulated saliva.…”
Section: Impact Of Sialorrhoea In Adult Neurological Diseasesmentioning
confidence: 99%
“…23,24,28,31,39,43,50,51 Individuals with non-tremor dominant PD phenotypes were at higher risk of drooling. 31,52 The precise contribution of these factors remains unsettled. The uncertainty rests partly on general issues above regarding why estimates of drooling prevalence and flow rates exist, but variability in individual profiles of impairment and disability also contributes.…”
Section: Risk Factors For Drooling In Pdmentioning
confidence: 99%
“…When motor, age and duration variables are controlled, LDDE appears no longer associated with drooling severity. 23,24,52 Proulx et al 38 found an association of l-dopa and hyposalivation, but Persson et al 56 observed no differences in salivary secretion rate between pwPD and controls, nor between subgroups of pwPD taking versus not taking dopaminergic medication. Bagheri et al 45 established no difference in salivary flow rates between treated and de novo pwPD.…”
Section: Risk Factors For Drooling In Pdmentioning
confidence: 99%